Anesthesia Techniques for Harvesting via Follicular Unit Excision - Barusco, Marco N. (Facial Plastic Surgery, 2023)
Follicular unit excision (FUE) is one of the established techniques for harvesting donor hair for hair transplantation. Traditionally, hair restoration surgery is performed using local anesthesia, although some surgeons use general anesthesia for the procedure. Normally, local anesthesia is coupled with light oral sedation to make the procedure more comfortable for patients. Techniques such as “ring block” or nerve blocks are common and effective for scalp anesthesia. Due to its simplicity, adequate pain control and safety, ring blocks are typically used for FUE donor harvesting, reserving nerve blocks only to patients who cannot be adequately anesthetized with the ring block. Using the correct technique for application of local anesthesia can dramatically decrease the pain associated with it and create a comfortable and easy experience for the patient.
Keywords: follicular unit excision; anesthesia; sedation; ring block; nerve block; donor harvesting; donor area